Your pain is not mine: A critique of clinical empathy - Stefanello, Eugenia (Bioethics, 2022)
Both in mainstream culture and in bioethical literature, there is a general agreement on the absolute positive value assigned to empathy in healthcare settings. Thanks to its two components—affective and cognitive—clinical empathy should allow physicians to be emotionally affected by the experiences of their patients, and at the same time, to imagine their situations in order to gain a deeper understanding and implement a ‘tailored’ approach to care. So, it seems that good physician has become synonymous with empathetic physician. However, while acknowledging its numerous benefits, I will argue that clinical empathy seems to harbour some dark sides. First, the affective component of clinical empathy (i.e. emotional resonance) is responsible for its partial nature and can lead to cognitive and moral distortions. Moreover, it can lead healthcare providers to negative psychological states, such as burnout and personal distress. Second, the cognitive component of empathy can be problematic as well: perspective-taking is a far more difficult task than it is ordinarily thought to be. I will also try to demonstrate that accessing the inner world of others is neither possible nor desirable since this operation can result in undermining the patient's agency. Third, clinical empathy can become a tool that disguises the power imbalance between patients and doctors, and this can reinforce an elitist and paternalistic conception of the clinical encounter. Furthermore, the disregard for the influence that the sociocultural context has on the clinical relationship can amplify and promote instances of epistemic injustice perpetuating discriminatory and unfair dynamics.